Enhanced focal cortical dysplasia detection in pediatric frontal lobe epilepsy with asymmetric radiomic and morphological features - Zhang, Manli; Yu, Hao; Cao, Gongpeng; Huang, Jinguo; Lu, Yanzhu; Zhang, Jing; Liu, Nana; Zhang, Wenjing; Cheng, Yintao; Kang, Guixia; Cai, Lixin (Frontiers in Neuroscience, 2023)
Objective: Focal cortical dysplasia (FCD) is the most common pathological cause for pediatric epilepsy, with frontal lobe epilepsy (FLE) being the most prevalent in the pediatric population.We attempted to utilize radiomic and morphological methods on MRI and PET to detect FCD in children with FLE.Methods: 37 children with FLE and 20 controls were included in the primary cohort, and a 5-fold cross-validation was performed. In addition, we validated the performance in an independent site of 12 FLE children. A two-stage experiments including frontal lobe and subregions were employed to detect the lesion area of FCD, incorporating the asymmetric feature between the left and right hemispheres. Specifically, for the radiomics approach, we used gray matter (GM), white matter (WM), GM and WM, and the gray-white matter boundary regions of interest to extract features.Then, we employed an Multi-Layer Perceptron classifier to achieve FCD lesion localization based on both radiomic and morphological methods.The Multi-Layer Perceptron model based on the asymmetric feature exhibited excellent performance both in the frontal lobe and subregions. In the primary cohort and independent site, the radiomics analysis with GM and WM asymmetric features had the highest sensitivity (89.2% and 91.7%) and AUC (98.9% and 99.3%) in frontal lobe. While in the subregions, the GM asymmetric features had the highest sensitivity (85.6% and 79.7%). Furthermore, relying on the highest sensitivity of GM and WM asymmetric features in frontal lobe, when integrated with the subregions results, our approach exhibited overlaps with GM asymmetric features (55.4% and 52.4%), as well as morphological asymmetric features (54.4% and 53.8%), both in the primary cohort and at the independent site.